Seasonal Distribution of Active Ectomycorridzal Roots in Natural forest of Pinus roxburghii - Singh, Asha; Lakhanpal, T. N. (Indian Forester, 2005)
The results of present study on ectomycorrhizal distribution and physico-chemical properties of three different soil layers of P. roxburghii forest have shown occurrence of more number of mycorrhizal roots during rainy season. The humus layer was observed to support more number of ectomycorrhizal roots. The nutrients (NPK) content in different soil layers were found to be higher during rainy season possibly due to occurrence of more number of acive mycorrhizae.